Integrated finite strip flutter analysis of bridges. (February 2019) - Naderian, Hamidreza; Cheung, Moe M.S.; Mohammadian, Majid; Dragomirescu, Elena
Highlights: IFSM is extended to the aerodynamic 3D flutter analysis of bridges. The solution falls into the category of multi-mode and full-mode flutter analysis. The convergence rate of the method is very high. An optimal scheme is proposed for solving the flutter eigenvalue problem. A simple technique is developed in order to handle different end conditions. Abstract: The recently developed integrated finite strip method (IFSM) is extended to the aerodynamic flutter analysis of bridges under wind effects. The methodology is capable of performing a three-dimensional (3D) flutter analysis in the IFSM environment, and the solution falls into the category of both multi-mode and full-mode flutter analysis. Aerodynamic stiffness and damping matrices, as well as structural property matrices, are derived by IFSM. In addition, an optimal scheme is proposed for solving the flutter eigenvalue problem. Furthermore, a simple technique has been developed in order to handle different end boundary conditions. The proposed finite strip solution is very straightforward in terms of amount of input data, boundary conditions, modeling, and the flutter analysis process. Moreover, the convergence rate of the method is very high due to the semi-analytical and localization nature of the IFSM. Benchmark numerical investigations are presented, including the study of a simply supported thin flat shell and a model of the Kap Shui Mun Bridge, an existing long-span cable-stayed bridge. The numerical results show that IFSM significantly improves the convergence of the critical flutter frequencies, and therefore leads to smaller storage requirements and faster flutter eigenvalue extraction.